STRATEGI PENGEMBANGAN WISATA GUA LIANG BANGKAI SEBAGAI CAGAR BUDAYA LOKAL, KABUPATEN TANAH BUMBU, KALIMANTAN SELATAN - Sapitri, Hawita (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2026)
Liang Bangkai Cave, located in Tanah Bumbu Regency, South Kalimantan, is a natural and cultural site with important historical and archaeological value for the development of sustainable tourism in Indonesia. This study aims to analyze the potential, roles of the government and community, and development strategies for Liang Bangkai Cave as a local cultural heritage site and conservation-based educational tourism destination. The research method used is descriptive qualitative with data collection techniques through field observations, in-depth interviews with the community, tourism managers, and the local government, as well as documentation studies from various related literature and archives. The results show that Liang Bangkai Cave has great geological and archaeological potential, such as natural stalactite and stalagmite formations and findings of ancient human artifacts that show traces of prehistoric life. However, this potential has not been optimized due to limited infrastructure, lack of promotion, and low community participation in tourism management. Therefore, the development strategy is directed at implementing the concept of eco-cultural tourism that emphasizes a balance between environmental conservation, cultural education, and local community empowerment. The government plays a role in policy, supervision, and infrastructure development, while the community is involved as the main actor in tourism management and promotion. With a well-planned and collaborative strategy, Liang Bangkai Cave has the potential to become a cultural tourism icon in South Kalimantan, not only improving the community's well-being but also preserving the nation's historical and cultural heritage.